Komitmen Organisasi yang dipengaruhi Pelatihan, Motivasi, Kepemimpinan, dan Kepuasan Kerja - Suandi Tegar Pratama; Aris Budiono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research focuses on the efficiency and effectiveness of employee treatment during a new era by managing training, motivation, leadership, and job satisfaction, which is expected to increase organizational commitment so that the organization can adapt to fundamental and permanent changes in the company. Research data was developed using a Likert scale. By using the Rosco table, research data was obtained for 100 respondents, not including the 30 people who were intended to test validity and reliability. We use quantitative methods with multiple linear regression. The IBM SPSS 24 statistical application was used for statistical calculations. This research shows that the four independent variables that have a partial impact on organizational commitment, training, and motivation do not significantly influence organizational commitment, leadership, or employee job satisfaction were found to have a significant influence on organizational commitment.